2020
DOI: 10.3389/fphys.2020.00988
|View full text |Cite
|
Sign up to set email alerts
|

Isoquercitrin Delays Denervated Soleus Muscle Atrophy by Inhibiting Oxidative Stress and Inflammation

Abstract: Although denervated muscle atrophy is common, the underlying molecular mechanism remains unelucidated. We have previously found that oxidative stress and inflammatory response may be early events that trigger denervated muscle atrophy. Isoquercitrin is a biologically active flavonoid with antioxidative and anti-inflammatory properties. The present study investigated the effect of isoquercitrin on denervated soleus muscle atrophy and its possible molecular mechanisms. We found that isoquercitrin was effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…It is widely activated during muscle atrophy and leads to muscle mass loss in varying degrees (28). Our previous study also found that ALS is widely activated in the process of denervation-induced muscle atrophy (6,12,14). The results of this study also confirm our previous results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is widely activated during muscle atrophy and leads to muscle mass loss in varying degrees (28). Our previous study also found that ALS is widely activated in the process of denervation-induced muscle atrophy (6,12,14). The results of this study also confirm our previous results.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that ubiquitin-proteasome system and autophagy lysosomal system are activated in the process of denervationinduced muscle atrophy, but the trigger factors that initiate their activation are not yet clear. Our previous studies suggested that oxidative stress and inflammation may be the trigger factors for activation of the ubiquitin-proteasome and autophagy lysosomal systems (6,18,31). Further studies are needed to confirm the possible molecular mechanism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have demonstrated that oxidative stress can cause inflammation, but no inflammation occurs during cell apoptosis ( 41 , 42 ). Inflammation will further aggravate oxidative stress and IL-6 can play an important role through the JAK/STAT3 pathway ( 43 ). In the present study, oxidative stress was caused by glucose fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation contributes to muscle atrophy development in several contexts [ 241 ]. Its early activation after denervation might be related to nerve injury and stump degeneration [ 242 ] and/or to the early increase in muscle levels of oxidative stress, as suggested by the upregulation of cytochrome P450 and monooxygenase transcripts, together with others involved in the anti-oxidant defense, about 3 h after denervation [ 87 , 243 ]. Activation of NF-κB and pro-inflammatory cytokines, secondary to de novo expression of connexins after one-week denervation, also contributes to muscle atrophy [ 213 ].…”
Section: Involvement Of Costamere Components In Different Muscle Amentioning
confidence: 99%